One Step Forward, Two Steps Back?: Relationship Recognition in Canadian Law Post-Same-Sex Marriage - Gaucher, Megan (Atlantis)

(untitled) (Mount Saint Vincent University, 2014)
This paper argues that same-sex marriage has been legalized through a problematic process of drawing parallels between gay and straight couples, ultimately creating new tensions between the conjugal and non-conjugal. As a result, the Canadian state’s continued reliance on conjugality as the primary non-blood relationship has implications for how we understand family. Using a sexual citizenship framework, this paper aims to conceptualize a direction for the Canadian state with respect to relationship recognition and to establish a space for discussing alternative categories of adult personal relationships.